PERBANDINGAN PEMBERIAN RINGERFUNDIN DENGAN RINGER LAKTAT COLOAD (SAAT) ANESTESI SPINAL DALAM MENCEGAH HIPOTENSI PADA PASIEN SEKSIO SESAREA ELEKTIF - , Orizanov Mahisa, Dr. IG Ngurah Rai Artika, SpAn, KAKV. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Hypotension is the most common complication in spinal anesthesia. One of the prevention effort is made by an administration of coloading crystalloid. This study aims to compare hypotension incidence in the coloading administration of Ringerfundin as an isotonic crystalloid and Lactated Ringer as a hypotonic crystalloid. Methods : This study was a double blind randomized controlled trials. Subjects were 82 pregnant women, who undergoing caesarean section with spinal anesthesia at Dr Sardjito Hospital in Yogyakarta, Panembahan Senopati Hospital in Bantul and Sleman Hospital. This study was done following institutional ethical committee approval and obtaining patients written informed consent. Patients who were selected had normal singleton pregnancy, more than 37 weeks gestation, 20-40 years old, BMI 20-30 kg/m2, height more than 145 cm, ASA 1-2. The exclusion criteria included patients with decreased lung compliance, preeclampsia, eclampsia, hypertension. Drop out criteria were total spinal, failed spinal. Subject sampling was conducted in consecutive sampling and block randomly. The patients were divided into two groups, group A (coloading 10 ml/kgbw Lactated Ringer ) and group B (coloading 10 ml/kgbw Ringerfundin). Fluid administration immediately after CSF detection in spinal needle. Fluid boluses for both grups were given via a 18G iv catheter with a fully open control valve and gravity alone providing the driving pressure. Hypotension monitoring was recorded every 2 minutes for the first 10 minutes following spinal. In addition, hypotension (25% decrease in baseline BP or SBP < 90 mmHg) could be treated Ephedrin and additional iv fluid boluses of Lactated Ringer. Results : There were no statistical significant differences (p=0.792) in hypotension incidence between Lactated Ringer and Ringerfundin coload administration. Conclusion : The coloading isotonic solution (Ringerfundin) has the similar effect compared to hypotonic solution (Lactated Ringer) to prevent hypotension in spinal anesthesia during elective caesarean section.